Cultural Transformations into Tourist Attraction - Rachman, Arief Faizal; Tekol, Y. C. (Graduate School, Universitas Brawijaya, 2020)
Marine-based culture performed social construction where local belief dominated and influenced daily basis culture. Selamatan Laut ritual was a sacred event where collecting spiritual power led by shamans. The focus of the research was to examine the cultural transformation of the ritual into a tourist attraction. In-depth interviews with seven members of the local community and a visitor enabled the researchers to explore the ritual practice. Analysis of the data revealed that the ritual was also scheduled cultural event calendar as a tourist attraction. The event attracted more tourists to grab income for locals and the region itself. There were physics and function cultural transformation at the ritual ceremony. The physical transformation included the establishment of tourist facilities. Meanwhile, functional transformation included the relation between actors in the community. Both physical and functional transformation relation created new social structures in the community. Local government dominantly played as an agent of change at the site. Local's community perceived the transformation of the event created new tourist attraction in Manggar, where scheduled events were being as a consensus between stakeholders. Keywords: cultural tourism, ritual, tourist attraction, transformation.